Heterogeneous Face Recognition from Facial Sketches (Informatica, 2021)
This paper presents a short summary of a dissertation thesis. The thesis presents a novel approach named X-Bridge for image-to-sketch translation for automatic heterogeneous face recognition. X-Bridge is based on a conditional adversarial network with an additional reconstruction path and a shared-latent space assumption between the original and the reconstruction path. With these modications, the results provided by X-Bridge overcome other state-of-the-art methods.